Clinical symptoms and risk factors comparison of ischemic and hemorrhagic stroke - Rosa De Lima Renita Sanyasi; Rizaldy Taslim Pinzon (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2018)
Backround: It is very important to know and detect various stroke symptoms because stroke is an emergency condition. Lack of knowledge about stroke symptoms leads to delay on stroke treatment.Objective: The aim of this study is to compare clinical symptoms and risk  factors between ischemic and hemorrhagic stroke.Methods: This study was a case control study. The subjects in this study were ischemic and hemorrhagic stroke patients. Subject data were recorded in electronic stroke registry at Bethesda Hospital, Yogyakarta.Results: The most common clinical symptoms in both groups were limb weakness (76.4% vs 71.4%), whereas the rarest was face drooping (2% vs 3.6%). Hypertension was the most common risk factor in both group (48% vs 71.4%), whereas atrial fibrillation was the rarest. This study did not find the specific correlation between any clinical symptoms to ischemic stroke incidence, however, decrease a level of consciousness was significant to hemorrhagic stroke incidence (OR: 2.738, 95% CI: 1.503-4.990, p: 0.001). Previous stroke (OR: 2.413, 95% CI: 1.314-4.433, p: 0.005) and dyslipidemia (OR: 4.862, 95% CI: 2.613-9.045, p: 0.000) were significant increasing risk of ischemic stroke. Hypertension was only the significant increasing risk of hemorrhagic stroke (OR: 3.680, 95% CI: 2.086-6.492, p: 0.000).Conclusion: Decrease level of consciousness has a significant correlation to hemorrhagic stroke incidence, but there is no specific symptom correlate to ischemic stroke incidence. Previous stroke and dyslipidemia are significant risk factors for ischemic stroke, whereas hypertension is the only significant risk factor for hemorrhagic stroke.